Directed evolution of protease beacons that enable sensitive detection of endogenous MT1-MMP activity in tumor cell lines - Jabaiah, Abeer (2011)
Directed evolution was applied to identify peptide substrates with enhanced hydrolysis rates by MT1-MMP suitable for protease beacon development. Screening of a random pentapeptide library, using two-color CLiPS, yielded several substrates identical to motifs in distinct collagens that shared the consensus sequence P-x-G↓L. To identify substrates with enhanced cleavage rates, a second-generation decapeptide library incorporating the consensus was screened under stringent conditions, which resulted in a MxPLG↓(M)/(L)M(G)/(A)R consensus motif. These substrates are hydrolyzed by human-MT1-MMP up to six times faster than reported peptide substrates and are stable in plasma. Finally, incubation of soluble protease beacons incorporating the optimized substrates, but not previous substrates, enabled direct detection of endogenous MT1-MMP activity of human-fibrosarcoma (HT-1080) cells. Extended substrate libraries coupled with CLiPS should be useful to generate more effective activity probes for a variety of proteolytic enzymes.